Waiting times in healthcare : a literature review - Söderlund, Riitta (Inderscience, 2025)
Waiting times in healthcare are a major challenge in many countries. The objective of this literature review was to form a comprehensive understanding of studies on waiting times in healthcare, especially in which healthcare areas and why the issue has been studied. For data searching, a multi-scientific database and the keywords waiting time and waiting lists were used. There were 95 articles included in the review. Two-thirds of the articles handled waiting times for surgical procedures or hospital care. None of the articles analysed waiting for visiting a general practitioner. Regarding the study purposes, one-sixth of the articles were related to clinical outcomes or patient satisfaction. The rest focused on policy and management issues of waiting times. Studies on waiting times for primary care are needed. For better management, research on information management of waiting times data is of great importance.